Environmental Innovations: Institutional Impacts on Co-operations for Sustainable Development - Helmut Karl; Antje Möller; Ximena Matus; Edgar Grande; Robert Kaiser (Fondazione Eni Enrico Mattei (FEEM), 2005)
A suitable strategy for achieving sustainable development is to foster environmental innovations. Environmental innovations, however, suffer from so-called double externalities, because apart from innovation spillovers they also improve the quality of public environmental goods, which can be used without cost by free riders. Those innovation spillovers can be avoided through co-operation. Furthermore co-operations can be considered as advantageous because environmental innovations often depend on interaction in research and development, production, selling and disposal. This paper analyzes as to what extent institutional factors impact co-operative arrangements of innovative organizations in the development of new environmental technologies. It applies a multi-dimensional institutional analysis focusing not only on institutional arrangements which exist among organizations but also on opportunities and constraints provided by the institutional environment in which these organizations are embedded. Expanding the existing research we will conclude what kind of policy measure may support the success within networks of environmental oriented innovators.
Keywords: L14; O31; Q55; Q58; 330; Environmental innovation; Co-operation; Sustainability; Institutional analysis; Policy measures